Out of Sight, Out of Mind? Ethical Issues Relating to the Use of Autonomous Armed Drones in Promotional Videos. (2nd October 2022) - Burt, Peter
Abstract : This article considers how autonomous drone systems are portrayed in three promotional videos published by military-industrial advocates of such technology. The videos are reviewed to explore ethical issues relating to armed drones and autonomous systems in warfare. The manner in which each video depicts technology, humans, and human-machine interactions is analysed in the context of sociotechnical imaginaries to examine how the videos reflect attitudes relating to the ethics of automation and warfare. It is concluded that the videos present uncertainties and ambiguities about autonomous weapons as certainties and simple choices. Issues which are not covered may be as important as the material and imagery presented. Rather than adding to public understanding over the issues surrounding autonomous weapons, concerns are presented in a selective and sanitised manner which avoids controversy and ultimately manipulates the opinions of the viewer, contributing to the creation of a sociotechnical imaginary which downplays ethical concerns.